Aberrant carotid artery injury during myringotomy. (September 2016) - Gnagi, Sharon H.; Chong, Brian W.; Schraff, Scott A.
Abstract: Myringotomy is a commonly performed procedure amongst otolaryngologists. Hemorrhage during myringotomy, albeit rare, can be devastating. Because bleeding during myringotomy is typically minimal if at all, otolaryngologists must be suspicious of a vascular injury if hemorrhage during myringotomy is encountered. Knowledge of vascular anatomy and potential variations is critical for prompt recognition of injury and timely management if injury should occur. Appropriate treatment includes initial control of bleeding followed by imaging to evaluate for vascular anomaly and/or injury. This will guide further treatment which may include embolization, surgical ligation, or bypass grafting.